PENGARUH PUPUK KANDANG AYAM DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) DI TANAH INSEPTISOL - Moita Hanna Rotua; Wardati Wardati; Arnis En Yulia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The study aims to determine the effect of chicken manure and spacing, and to obstain interactionthe best doses of chicken manure and spacing for growth and production of shallots.This research has been carried in Experimental Station Faculty of Agriculture University of Riau from October 2017 to January 2018. This research was conducted in a factorial which was arranged in a complete randomized design consisting of 2 factors and 3 replications. The first factor is chicken manure which is without chicken manure, 10 ton.ha-1, 20 ton.ha-1 and 30 ton.ha-1, and the second factor is spacing of 10 cm x 15 cm, 15 cm x 15 cm and 20 cm x 15 cm. The data obtained were further tested by Duncan's Multiple Range Test 5%. The interaction chicken manure and spacing were significant in increasing fresh tuber weight and tuber weight worth keeping and the interaction of chicken manure application and spacing was not significant in increasing plant height, number of leaves per clump, number of tubers per clump and tuber wrap. The giving of chicken manure at a dose of 30 ton.ha-1 and a spacing of 20 cm x 15 cm resulted in a tuber weight worth the highest, namely 1193,80 g.m-2(11,938 ton.ha-1)Keywords: Shallot, chicken manure, plant spacing and soil Inceptisol